In situ formation of polymer electrolytes using a dicationic imidazolium cross-linker for high-performance lithium ion batteries. Issue 9 (10th February 2021) - Tseng, Yu-Chao; Hsiang, Shih-Hsien; Tsao, Chih-Hao; Teng, Hsisheng; Hou, Sheng-Shu; Jan, Jeng-Shiung
Abstract : A dicationic imidazolium cross-linker is designed and further adopted as an electrolyte for lithium ion batteries. Abstract : Improving the electrochemical performance of polymer electrolytes in lithium ion batteries has been intensively studied. Herein, we adopted an in situ solventless polymerization strategy to fabricate PEG-based electrolytes cross-linked by a dicationic imidazolium compound directly onto the lithium anode, providing a direct, effective, and versatile pathway for the preparation of electrolytes. The electrolytes exhibit high thermal stability, a wide electrochemical window, an ionic conductivity higher than 10 −4 S cm −1 and an outstanding deformation stability without cracking at a 60% compressive strain. A conformal attachment at the electrolyte/electrode interface and a superior charge–discharge capacity as well as a long cycle life at 25 °C (0.2C rate, 93.8% after 150 cycles) and 60 °C (0.5C rate, 94.6% after 100 cycles) can be achieved in the equipped Li/LiFePO4 cell by forming electrolytes on lithium metal directly, which represents a promising approach for next-generation lithium ion battery technologies.